The Guideline for Development Learning Administration in The New Normal Era of Schools Under Maha sarakham Primary Educational Service Area Office 1: The Guideline for Development Learning Administration in The New Normal Era of Schools Under Maha sarakham Primary Educational Service Area Office 1 - Wayopat, Nattawut; Duangchatom, Kritkanok (RATANABUTH JOURNAL, 2023)
The purposes this research were to 1) study the current conditions, desirable condition and need assessment of learning administration in the new normal era of schools under Maha sarakham primary educational service area office 1. 2) study guideline for development learning administration in the new normal era of schools under Maha sarakham primary educational service area office 1. The research was divided into 2 phases: Phase 1 study the current conditions, desirable condition and need assessment of learning administration in the new normal era of schools. The sample group were 320 school administrators and teachers. The research instrument were questionnaires, discrimination was 0.32–0.87, reliability of .84. The statistics used for data analysis were mean and deviation standard. Phase 2: study guideline for development learning administration in the new normal era of schools. The target groups include 7 experts for assess suitability possibility of guideline. The research instrument were interview form and assessment form of guidelines The results of the research were as follows: The current state in overall was low level, the desirable state in overall was in the highest level. The need assessment rank from high to low level was 1) teaching and learning, 2) teacher development, 3) educational evaluation, 4) new resource management, 5) curriculum administration. 2. The guideline for development learning administration in the new normal era of schools, Include was 1 principles, 2) objectives, 3) contents, 4) development activities, and 5) measurement and evaluation. The Content consists of 5 modules, Include, Module 1 teaching and learning, Module 2 teacher development, Module 3 educational evaluation, Module 4 new resource management, Module 5 curriculum administration, Summary of guidelines evaluation, feasibility and utility was the highest in overall.